Wind tunnel testing to study turbulent wind field effect on wind load and wind-induced response of TV tower - Xia, Daqiao; Pei, Cheng (Frontiers in Built Environment, 2025)
For steel-constructed TV towers, complex aerodynamic profiles and low damping are typical characteristics—two attributes that render wind-induced response and wind load critical considerations in their design. Additionally, their wide distribution across diverse terrains exposes these structures to varied wind conditions, further complicating wind-resistant design efforts. To explore how wind field parameters affect wind load and wind-induced response, this study took a 240-m-high TV tower as the engineering background, simulated different turbulent wind fields in a wind tunnel, conducted force measurement tests using a high-frequency dynamic balance (with the model segmented into seven sections to improve accuracy), calculated via the equivalent static wind load (ESWL) method (considering the first three modes), and verified with the complete quadratic combination (CQC) method. Results within the tested range show that mean wind force decreases with increasing turbulence intensity, while the root mean square (RMS) of wind force increases correspondingly; conversely, the RMS of the tower’s wind-induced response decreases as turbulence intensity rises. These findings highlight the need to comprehensively consider mean and fluctuating wind effects and their impact on structural response in the wind-resistant design of steel TV towers.